2021
DOI: 10.1186/s13148-021-01039-z
|View full text |Cite
|
Sign up to set email alerts
|

BET bromodomain inhibitors PFI-1 and JQ1 are identified in an epigenetic compound screen to enhance C9ORF72 gene expression and shown to ameliorate C9ORF72-associated pathological and behavioral abnormalities in a C9ALS/FTD model

Abstract: Background An intronic GGGGCC (G4C2) hexanucleotide repeat expansion (HRE) in the C9ORF72 gene is the most common cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), referred to as C9ALS/FTD. No cure or effective treatment exist for C9ALS/FTD. Three major molecular mechanisms have emerged to explain C9ALS/FTD disease mechanisms: (1) C9ORF72 loss-of-function through haploinsufficiency, (2) dipeptide repeat (DPR) proteins mediated toxicity by the translation of the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Furthermore, BET proteins have also been associated with cognitive dysfunction and neuropsychiatric diseases, such as SUD, FTD, and schizophrenia [ 16 , 153 , 192 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, BET proteins have also been associated with cognitive dysfunction and neuropsychiatric diseases, such as SUD, FTD, and schizophrenia [ 16 , 153 , 192 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting data were recently obtained by Quezada and collaborators, showing that the BET inhibitor PFI-1 induced V1-V3 transcripts of the mutant C9ORF72 gene and facilitated the formation of nuclear RNA foci with a consistent reduction in DPR inclusions in cell models of C9ALS/FTD. In addition, BET blockade suppressed the hippocampal-dependent cognitive deficits in a C9BAC mouse model of C9ALS/FTD [ 153 ]. Hence, BET inhibitors could be considered as a valuable therapeutic approach for ALS and FTD, even though further studies are essential to better identify the effective dosage, as well as the long-term efficacy in the pathology progression.…”
Section: Involvement Of Bet Proteins In Neuropathological Conditionsmentioning
confidence: 99%
“…Therefore, we used SNORD118 -mutant human iPSC-derived NPCs and performed cell-based small-molecule screen for reversing proliferation defects in mutant NPCs. On the basis of published studies, we selected those chemical compounds that potentially affect ribosome biogenesis and nucleoli functions, including 2BAct ( 38 ), MCL-186 ( 39 ), bromosporine ( 40 ), nicotinamide ( 41 ), tideglusib ( 42 , 43 ), PFI-1 ( 44 ), YM201636 ( 45 ), cilostazol ( 46 ), leucine ( 47 ), and prostetin ( 48 ). Our initial EdU assay–based cell proliferation screen identified 2BAct, MCL-186, and cilostazol, which significantly increased the proliferation of SNORD118 *5C>G -mutant NPCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These screens have been carried out in experimental models of frontotemporal dementia (FTD) (i.e., expressing hexanucleotide repeat expansion in the C9ORF72 gene), the second most common dementia after AD [ 125 ] that exhibit alterations in the repressive marks H3K9me3, H3K9me27 and DNA methylation in neurons and astrocytes [ 126 , 127 , 128 , 129 ]. In some of these studies, treatment with a specific class of epidrugs (i.e., JQ1 and PFI-1, both members of the bromodomain and extra-terminal domain (BET) inhibitor family) was shown to restore gene transcription in mouse and human iPSC-derived neurons, and moreover, to ameliorate cognitive deficits in FTD mice [ 130 , 131 ]. However, in a comparable JQ1 treatment it was shown that this BET inhibitor can inhibit non-spatial learning in wild-type mice [ 132 ], indicating that additional studies that precisely determine the genomic regions affected by JQ1 treatment are required.…”
Section: Alterations In the Epigenome And 3d Chromatin Architecture D...mentioning
confidence: 99%